Recognition of the neutral sugars conversion induced by bacterial community during lignocellulose wastes composting. (December 2019) - Chen, Xiaomeng; Zhao, Xinyu; Ge, Jingping; Zhao, Yue; Wei, Zimin; Yao, Changhao; Meng, Qingqing; Zhao, Ran
Graphical abstract: Highlights: Each neutral sugar is converted by a specific group of bacteria in RS composting. A group of bacteria can convert multiple neutral sugars during MD and L composting. The diversity of bacterial community lead to the difference in the conversion. The GM/AX is found to characterize the neutral sugars conversion during composting. Abstract: The aim of this study was to explore the conversion characteristics of neutral sugars during different lignocellulose wastes composting from rice straw (RS), leaf (L) and mushroom dreg (MD). The results showed that the changes of neutral sugars were different during different wastes composting, but the changes of various hexose or pentose were similar during composting of the same material. The diversity of bacterial community led to different conversion characteristics of neutral sugars. During RS composting, each neutral sugar was transformed by a specific group of bacteria. However, a group of bacteria could transform multiple neutral sugars during MD and L composting. Furthermore, GM/AX value was first applied to composting, which could be used to characterize the conversion of neutral sugars during composting. This will help to provide more efficient recommendations for lignocellulose wastes treatment and accelerating humic substances synthesis during composting.